Pengaruh Entrepreneurial Leadership Terhadap Kinerja IKM Batik Jambi dengan Perilaku Kerja Inovatif Sebagai Variabel Intervening - Melani Kadar; Vivi Usmayanti; Febby Nanda Utami; Yossinomita (LPPM Universitas Dinamika Bangsa, 2023)
This study aims to determine the direct and indirect influence of entrepreneurial leadership on the performance of Batik Jambi small and medium industries, with innovative work behavior as an intervening variable. The research sample used was 84 respondents who were selected through a simple random sampling technique and tables for determining the number of samples of Isaac and Michael. Data collection in this study used a questionnaire with an ordinal scale format, where the data obtained was then analyzed using the partial least squares path modeling (PLS) technique. The results of the direct effect test prove that entrepreneurial leadership has a significant effect on innovative work behavior, while entrepreneurial leadership has no significant effect on the performance of Batik Jambi small and medium industries. Then innovative work behavior has a significant effect on the performance of Batik Jambi small and medium industries. For the mediating effect of innovative work behavior variables, it is proven that innovative work behavior can mediate the indirect effect of entrepreneurial leadership on the performance of Batik Jambi small and medium industries.